Analysis of the Symbolic Meaning and Cultural Identity in Sarolangun Batik Arts Jambi Province - Padma Dewi; Budiwirman Budiwirman (International Journal of Educational Dynamics, 2020)
The purpose of this study is to analyze the symbolic meaning and cultural identity of batik. The symbolic meaning of a form of batik motifs gives signs to represent the cultural character of Sarolangun District. Cultural identity acts as a mediation of interaction by the Sarolangun district community to be known in the outside the world. This research method uses descriptive qualitative method. The approach taken is semiotics by Charles Piers.The results of the Semiotics Peirce concept can distinguish the meaning of batik based on the shape of the batik motif and the sign found in the decoration. The symbolic meaning of a number of batik motifs are found in the theme of Mato Punai, Cik Minah edge motif, quaint bird. Mato Punai is a bird's eye motif as a symbol of prosperity. Cik Minah edge motif symbolizes the agility of a woman in life. There are 18 batik motifs that have been recognized and has been patents, hereby that Sarolangun batik arts has its own identity for Saroalngun district culture.